Role of CD68 immunohistochemistry in categorizing benign nonmesothelial cell population and refining "atypical" category in serous fluid cytology. Issue 12 (9th July 2020) - Savari, Omid; Jassim, Sarmad; Ferrer, Hector; Ganocy, Stephen J.; Ganesan, Santhi
Abstract: Background: Body fluids are rich in histiocytes and may mimic atypical epithelial cells morphologically. Histiocytes can pose a significant challenge in serous fluid cytology as they tend to appear atypical due to prolonged accumulation in serous fluids in vivo and processing by liquid‐based cytology in vitro . Not many studies have documented the utilization of histiocytic marker such as CD68 in serous fluid cytology, which can subsequently reduce the "atypical" diagnostic category. Methods: One thousand one hundred and twenty‐nine cases of serous fluid cytology from 2016 to 2019 were reviewed and reclassified based on proposed classification of the international system for reporting serous fluid cytology. There were 133 cases with atypical diagnoses, out of which 51 cases had cellblocks. An immunohistochemistry (IHC) panel, including two mesothelial markers, two epithelial markers, and one histiocytic marker was applied to the atypical samples. Same IHC panel was utilized to evaluate 15 cases each from negative for malignancy (NFM), suspicious for malignancy (SFM), and malignant (MAL) categories for further comparison. Results: After reevaluation of the cytology material with IHC stains, 924 (82%), 133 (12%), 23 (2%), and 49 (4%) of the cases were reclassified as NFM, atypia of uncertain significance, SFM, and MAL, respectively. Twenty‐five out of 51 atypical cases (49%) were downgraded to "benign" after reevaluation with CD68 IHC. Conclusion: Histiocytes can mimic atypical epithelial cells in body fluids. Effective utilization of CD68 IHC will be beneficial in further refining the "atypical" diagnostic category in serous fluid cytology.